The Coefficients Of Functions With Positive Real Part And Some Special Classes Of Univalent Functions. - M. Ali, Rosihan (2003)

(untitled)
Several special classes of univalent functions f in the unit disk U are characterized by the quantity zf'(z)/ f (z) lies in a given region in the right-half plane. Amongst these are the classes SS• (a) of strongly starlike functions of order a and PS• (p) consisting of parabolic starlike functions of order p. Both classes are closely related to the class P of nonnalized analytic functions in U with positive real part.